A prospective comparative study of outcome between open lichtenstein versus laparoscopic repair of inguinal hernia - Choudhary, Sushila; Soni, Hitesh; Mehta, Jagdish M.; Kalia, Saurabh (International Journal of Research in Medical Sciences, 2021)
Background: Laparoscopic hernia repair is technically difficult and has long learning curve than open repair. Moreover, with increased cost of procedure do patient really get benefited in terms of intraoperative time duration, post-operative pain and complications, length of hospital stays, and time taken to return to usual activity needs to be studied. Methods: In this prospective observational study of 100 patients including unilateral, bilateral, direct and indirect inguinal hernia and excluding obstructed and strangulated hernia, 61 patients underwent open repair and 39 patients underwent laparoscopic hernia repair. Pain analysis was done with visual analogue scale. Unpaired student T test and Chi square test used (p<0.05). Results: Baseline characteristics age, sex of the two groups were similar. Mean operative time in laparoscopic group was 105.38±35.13 minutes and in open group was 79.95±31.12 minutes (p<0.001). There was statistically significant difference in mean pain score of laproscopic verses open techniques (p<0.001). Urinary retention was the most common post-operative complication in both groups but was statistically not significant. Mean hospital stay in laparoscopic group was 1.56±0.50 days and in open group was 1.9±0.50 days (p-0.002). Mean time taken to return to usual activity in open repair was 41.10±27.15 days and in laparoscopic group was 16.23±6.37 days (p-0.001). Conclusions: This study showed that in laparoscopic repair of inguinal hernia patients have less post-operative pain, shorter hospital stays and early return to work. However, the laparoscopic technique had longer operative time duration.